Resolução de problemas geométricos: um estudo sobre conhecimentos declarativos, desenvolvimento conceitual, gênero e atribuição de sucesso e fracasso de crianças dos anos iniciais do ensino fundamental - Tortora, Evandro [UNESP] (2014)
This research aims to investigate the relationship between declarative knowledge, conceptual development, gender and attribution for sucess and failure of students in the early years of Elementary School in solving geometrical problems. This study was developed in accordance with Attribution Theory of Causality (Weiner (1985)), studies of the Van Hiele Model of the Development of Geometric Thinking, the Theory of Geometric Skills Hoffer (1981), The formation of Concepts (Klausmeier Goodwin (1977) and Declarative Knowledge (Anderson (1983). The participants were 30 children from first to fifth year of Elementary School (3 boys and 3 girls each year). The instruments used were: 1) A semi-structured interview about learning and teaching 2) Assessment consists of 10 problems involving geometry, 3) A semi-structured interview about attribution for sucess and failure of students about their results in solving problems. Data were collected through video recording. Data analysis showed that: 1) The children have few declarative knowledge about the plain figures, which may have caused a loss in the level of conceptual development on planar ond spatial figures lying mostly in the concrete level of conceptual development 2) The participants had difficulties with respect to verbal skills, with limited vocabulary to explain their arguments, which is found mostly in the view level when the development of geometrical thinking 3) the causes of sucess and failure attribution students were related to the acquisition of knowledge or learning content, pay attention, memory, perception, belief in one's own ability and luck. In addition, students tend to attribute the causes of sucess and failure to internal factors, 4) gender or age of the students was not related to performance or level of conceptual development of students, the strongest influence them as to the performance problems was the fact that they have already study of geometric figures in...